Samuel Schelguigius S. Theol. D. et Prof. P. Athenai Gedanensis Rector et ad SS. Trinit. Pastor / C. G. Ludwig. - Ludwig, Christian Gottlieb (1675-ok. 1730) (1703)
Przedstawia portret w popiersiu Samuel Schelwig (1643-1715).